Halide bridged organophosphorus complexes of HgX2 (X: I, Br and Cl): Synthesis, structure and theoretical studies - Mondal, Jahangir; Manna, Amit Kumar; Patra, Goutam Kumar (European Journal of Chemistry, 2021)
Three organophosphorus mercury (II) coordination compounds [Hg2(µ-X)2X2(PPh3)2] X: I (1), Br (2), and Cl (3) have been synthesized by the reaction of mercury (II) halides with triphenylphosphine. The prepared complexes were characterized by spectroscopic techniques as well as by elemental analysis. The crystal structure of [Hg2(µ-I)2I2(PPh3)2] (1) was obtained by single-crystal X-ray diffraction study. Crystal data for [Hg2(µ-I)2I2(PPh3)2], C36H30Hg2I4P2: Monoclinic, space group P21/c (no. 14), a = 19.2115(13) Å, b = 11.1291(8) Å, c = 19.0599(14) Å, β = 90.461(2)°, V = 4075.0(5) Å3, Z = 4, T = 293.15 K, μ (MoKα) = 10.657 mm-1, Dcalc = 2.336 g/cm3, 46095 reflections measured (4.23° ≤ 2Θ ≤ 49.994°), 7182 unique (Rint = 0.0563, Rsigma = 0.0365) which were used in all calculations. The final R1 was 0.0322 (I > 2σ(I)) and wR2 was 0.0780 (all data). The single crystal analysis of [Hg2(µ-I)2I2(PPh3)2] complex revealed that it has dimeric structure with bridged halides. [Hg2(µ-I)2I2(PPh3)2] complex has also a supramolecular arrangement through I···H-C interactions. The crystal packing and supramolecular features of these coordination compounds have also been studied using geometrical analysis, Hirshfeld surface analysis and DFT studies. Hirshfeld surface analysis indicated that H···H (49.3%), C···H (10.6%), and I···H (12.8%) interactions are the primary contributors to the intermolecular stabilization in the crystal. The equilibrium geometries of the studied complexes are investigated theoretically at the B3LYP/LANL2DZ level of theory. The calculated energy gap between HOMO-LUMO orbitals for complexes 1, 2, and 3 are in the trend of complex 3 > 2 > 1.